Imaging multiple conductance states in an alamethicin pore. - Harriss, L; Cronin, B; Thompson, JR; Wallace, M (2011)
Alamethicin is the archetypal antimicrobial pore-forming peptide. Although the peptide has long been known to form pores of characteristic conductances in lipid membranes, the precise nature of these pores is not known. Simultaneous calcium-flux imaging and single-channel recording in a droplet interface bilayer allowed us to directly attribute multiple conductance states to a single point diffusing in the bilayer.